Rationing of total knee replacement: a cost-effectiveness analysis on a large trial data set. Issue 1 (30th January 2012) - Dakin, Helen; Gray, Alastair; Fitzpatrick, Ray; MacLennan, Graeme; Murray, David; ,
Abstract : Objectives: Many UK primary care trusts have recently introduced eligibility criteria restricting total knee replacement (TKR) to patients with low pre-operative Oxford Knee Scores (OKS) to cut expenditure. We evaluate these criteria by assessing the cost-effectiveness of TKR compared with no knee replacement for patients with different baseline characteristics from an NHS perspective. Design: The cost-effectiveness of TKR in different patient subgroups was assessed using regression analyses of patient-level data from the Knee Arthroplasty Trial, a large, pragmatic randomised trial comparing knee prostheses. Setting: 34 UK hospitals. Participants: 2131 osteoarthritis patients undergoing TKR. Interventions and outcome measures: Costs and quality-adjusted life years (QALYs) observed in the Knee Arthroplasty Trial within 5 years of TKR were compared with conservative assumptions about the costs and outcomes that would have been accrued had TKR not been performed. Results: On average, primary TKR and 5 years of subsequent care cost £7458 per patient (SD: £4058), and patients gained an average of 1.33 (SD: 1.43) QALYs. As a result, TKR cost £5623/QALY gained. Although costs and health outcomes varied with age and sex, TKR cost <£20 000/QALY gained for patients with American Society of Anaesthesiologists grades 1–2 who had baseline OKS <40 and for American Society of Anaesthesiologists grade 3 patients with OKS <35, even with highly conservative assumptions about costs and outcomes without TKR. Body mass index had no significant effect on costs or outcomes. Restricting TKR to patients with pre-operative OKS <27 would inappropriately deny a highly cost-effective treatment to >10 000 patients annually. Conclusions: TKR is highly cost-effective for most current patients if the NHS is willing to pay £20 000–£30 000/QALY gained. At least 97% of TKR patients in England have more severe symptoms than the thresholds we have identified, suggesting that further rationing by OKS is probably unjustified. Trial registration number: ISRCTN 45837371.